2021
DOI: 10.2486/indhealth.2020-0176
|View full text |Cite
|
Sign up to set email alerts
|

Effects of participatory workplace improvement program on stress-related biomarkers and self-reported stress among university hospital nurses: a preliminary study

Abstract: Although participatory workplace improvement programs are known to provide favorable effects on high stress occupations like nursing, no studies have confirmed its effect using biomarkers. The aim of this study was to determine whether a participatory workplace improvement program would decrease stress-related symptoms as evaluated by biomarkers and self-reported stress among hospital nurses. Three actions to alleviate job stress, which were determined through focus group interviews and voting, were undertaken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
0
9
1
Order By: Relevance
“…Although several in ammatory markers had decreased in Group 1 after the intervention, another physiological measure (ANA) remained unchanged in the same group. The plausible explanation is that positive outcomes may emerge at different timing in each measure [3]. Past participatory workplace intervention studies did not also obtain positive effects simultaneously in all stress-related measures they used in the intervention group [20][21][22]25], despite longer intervention period compared to our study.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Although several in ammatory markers had decreased in Group 1 after the intervention, another physiological measure (ANA) remained unchanged in the same group. The plausible explanation is that positive outcomes may emerge at different timing in each measure [3]. Past participatory workplace intervention studies did not also obtain positive effects simultaneously in all stress-related measures they used in the intervention group [20][21][22]25], despite longer intervention period compared to our study.…”
Section: Discussioncontrasting
confidence: 64%
“…Organizational-level participatory workplace intervention, which aims to improve work environment and employees' health, is more likely to produce sustainable effects than interventions targeting an individual because employees take an active part in identifying problems and giving possible solutions by themselves [1,2]. In our previous study, we reported that a 5-month lasting organizational-level participatory workplace intervention was effective in reducing stress-related in ammatory markers as represented by interferon (IFN)-γ, interleukin (IL)-6, and IL-12/23p40, and IL-15 among 31 Japanese female nurses [3]. During this course, we recognized that our intervention might have stimulated prosocial helping behaviors like giving social support to others in some participants.…”
Section: Introductionmentioning
confidence: 99%
“…We carried out a participatory workplace improvement intervention [9][10][11][12] from August 2017 to February 2018. Briefly, the participatory workplace improvement intervention is that employees at the workplace actively take part in identifying workplace problems, find feasible actions/solutions, and work towards improvement (detailed procedure is presented in our previous paper 2) ). We recruited nurses working at a hospital (n=144) in the southern part of Japan.…”
mentioning
confidence: 99%
“…Although several inflammatory markers had a decrease in Group 1 after the intervention, another physiological measure (ANA) remained unchanged in the same group. The plausible explanation is that positive outcomes may emerge at different timing in each measure 2) . Past participatory workplace intervention studies did not also obtain positive effects simultaneously in all stress-related measures they used in the intervention group [10][11][12] , despite a longer intervention period compared to our study.…”
mentioning
confidence: 99%
See 1 more Smart Citation